2013
DOI: 10.1017/jns.2012.30
|View full text |Cite
|
Sign up to set email alerts
|

Modelling potential β-carotene intake and cyanide exposure from consumption of biofortified cassava

Abstract: Vitamin A (VA) deficiency causes disability and mortality. Cassava can be crossbred to improve its β-carotene (BC) content; typical white cassava contains negligible amounts of BC. However, cassava contains cyanide and its continued consumption may lead to chronic disability. Our objective was to estimate the risk–benefit of consuming BC-enhanced cassava to increase VA intake. A total of ten American women were fed white and BC-enhanced cassava. BC and cyanide data from the feeding study were combined with Afr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…In addition, we provided a conservative estimate of the potential increases in vitamin A intake as we used cassava varieties with an average β-carotene concentration of 5•4 μg/g (fresh weight) for raw cassava and 3•9 μg/g (fresh weight) for cooked cassava and applied a conservative conversion factor of 7:1. Another study found a higher impact of adding yellow cassava to the diet but used different modelling assumptions regarding concentration, cooking method and intake quantity (4) . In our study, Fe and Zn were not identified as problem nutrients and this corresponds with the few children being Zn deficient (3 %).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we provided a conservative estimate of the potential increases in vitamin A intake as we used cassava varieties with an average β-carotene concentration of 5•4 μg/g (fresh weight) for raw cassava and 3•9 μg/g (fresh weight) for cooked cassava and applied a conservative conversion factor of 7:1. Another study found a higher impact of adding yellow cassava to the diet but used different modelling assumptions regarding concentration, cooking method and intake quantity (4) . In our study, Fe and Zn were not identified as problem nutrients and this corresponds with the few children being Zn deficient (3 %).…”
Section: Discussionmentioning
confidence: 99%
“…Biofortified yellow cassava, developed through conventional plant-breeding techniques, is a new staple food that is similar in use and nutritional content to white cassava but additionally contains substantially higher amounts of pro-vitamin A ( 2 ) . Yellow cassava could potentially increase vitamin A intake and reduce vitamin A deficiency, especially in remote rural areas where other interventions face challenges to reach people in need of vitamin A ( 3 , 4 ) .…”
mentioning
confidence: 99%
“…Cassava holds great promise for provitamin A biofortification [ 100 ]. However, limited studies have been conducted to evaluate its bioavailability and efficacy [ 22 ].…”
Section: Bioavailability Of Target Micronutrients In Biofortified mentioning
confidence: 99%
“…Results from the previous human study [11] were used to simulate the amount of vitamin A which would be consumed if all native white cassava were replaced with biofortified cassava. In a model based on these previous results, replacing native with biofortified cassava would provide over 90% of the recommended dietary intake of vitamin A [12]. …”
Section: Introductionmentioning
confidence: 99%